Experiencing English: A Textbook Evaluation on the Cultural Loads - Yunita Dewi Wahyuni; Novalia Rizkanisa; Iskandar Abdul Samad; Bukhari Daud (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
This research aimed at investigating the cultural contents implied in the English textbook entitled Experiencing English. A qualitative method was used in this research which analyzed the English textbook. The data source of this research was the English textbook for Junior High School students entitled Experiencing English. The instrument used for collecting data was only from documentation in form of textbook. Then the data were analyzed by using Byram et al. (1994) framework to investigate the aspects of culture. In this research analyzed the nine aspects that have to be included in the EFL textbook. The result showed that stereotypes and national Identity is more frequently used in experiencing English. This aspect represents the target culture stereotypes and national identity which is commonly focused on the British and American culture. Finally, the conclusion led to the cultural content that is frequently used in Experiencing English textbook is target language culture. Notwithstanding, the source/local culture values as drafted in the 2013 Curriculum is still implied in the textbook as intended to enable the students to reflect their own culture in English.